When multimodality cardiac imaging saves the day: rare cause of embolic strokes. Issue 1 (2nd January 2020) - Demetriades, Polyvios; Speke, Laura; Wilson, Lowella; Khan, Jamal Nasir
Abstract : Hypereosinophilic syndrome (HES) is a rare disorder characterised by eosinophilic infiltration of tissues. Myocardial infiltration occurs in 50%–60% of HES and leads to a condition called Loeffler's endocarditis. This can lead to endomyocardial injury with resultant superimposed thrombus formation and embolic stroke. We describe the case of a 57-year-old female patient presenting with neurological symptoms who was found to have multiple embolic strokes on a background of long-standing eosinophilia. Following a series of investigations, including transthoracic and transoesophageal echocardiographies and cardiovascular MRI, she was confirmed to have Loeffler's endocarditis with left ventricular thrombus. She was treated successfully with steroids and anticoagulation. We describe the pathophysiology of HES and Loeffler's endocarditis and stress the crucial role of multimodality cardiac imaging in establishing its diagnosis and treatment monitoring.